Acoustically Triggered Harvesting of Nanometer Airborne Particles – A Numerical Model for the Ultrasonic Manipulation - Rubinetti, D; Weiss, D (The International Journal of Multiphysics, 2018)
In this study, the focus is to model the physics of acoustic harvesting for 100 nanometer particles in order to lay the groundwork for technical feasibility studies. Based on a simplified 2D test-case channel geometry with an intense acoustic standing wave field the relevant drag and acoustic forces are reviewed and implemented in a numerical model. The standing wave is appropriately formulated to harvest particles in one single pressure antinode which conforms to the centerline of the channel. The particle trajectories along the chosen test-case channel have been analytically verified. Advancements in the acoustic manipulation of particles have mainly received attention for liquid carrier media. The conceived model is numerically stable and suitable to assess the potential of harvesting nanometer aerosols in gaseous environments.